Evaluating the mechanical and fire-resistance properties of modified fast-growing Chinese fir timber with boric-phenol-formaldehyde resin. (15th November 2017) - Yue, Kong; Chen, Zhangjing; Lu, Weidong; Liu, Weiqing; Li, Mengyu; Shao, Yaling; Tang, Lijuan; Wan, Li
Highlights: The activation energy of boric-containing PF was higher than that of common PF. High-frequency heating provided a rapid rise in temperature for BFP-specimen. The strength grade of modified wood with BPF resin was increased greatly. The fire performance of modified wood with BPF resin was improved significantly. Abstract: The abundant fast-growing Chinese fir was confined to nonstructural use for its poor mechanical and fire performance, and classified as low-quality building materials. Herein, Chinese fir was impregnated with boric-phenol-formaldehyde ( BPF ) resin, and then processed using high-frequency heating according to practical processing and application. The properties of BPF -specimen were tested, and the results showed, compared with the common plate hot pressing, high-frequency heating was an efficient technology for its high heating rate according to commercial process. Compared with the control, the mechanical properties and fire performance of BPF -specimen were improved obviously, and the more the resin retain, the better the properties of the modified specimen.